Political connections, corporate governance, and tax aggressiveness in Malaysia - Abdul Wahab, Effiezal Aswadi; Ariff, A.M.; Madah Marzuki, M.; Mohd Sanusi, S. (Emerald Group Publishing Limited, 2017)
Purpose: The purpose of this paper is to examine the relationship between political connections and corporate tax aggressiveness in Malaysia. In addition, this paper investigates the relationship between corporate governance variables and corporate tax aggressiveness. Next, the study investigates the mitigating role of corporate governance in the relationship between political connections and corporate tax aggressiveness. Design/methodology/approach: The sample of this study is based on 2,538 firm-year observations during the 2000-2009 periods. This study employs a panel least square regression with both period and industry fixed effects. The study retrieved the corporate governance variables from the downloaded annual reports, whilst the remaining data were collected from Compustat Global. Findings: This study finds that politically connected firms are more tax aggressive than non-connected firms. Furthermore, the study finds that large board size decreases the likelihood of tax aggressiveness and a non-linear relationship exists between institutional ownership and tax aggressiveness suggesting increase in monitoring as the ownership increases. However, the study finds no evidence to suggest that corporate governance mitigates the influence of political connections in promoting tax aggressiveness behavior. The findings suggest that the impact of political connections could outweigh the benefits of changes in corporate governance in Malaysia. Research limitations/implications: The data are not recent, but it reflects a rather longitudinal research period. Originality/value: This paper extends the literature of tax research in Malaysia which is in its’ infancy stage. Furthermore, it investigates the role of political connections in tax-planning research.